A recurrent solitary fibrous tumor of the thigh with malignant transformation: A case report - Yoshimura, Yasuo (Int J Surg Case Rep, 2016)
INTRODUCTION: We describe an unusual case of a uniformly high-grade malignant solitary fibrous tumor (SFT) of the thigh with recurrence after wide resection in a 31-year-old man. PRESENTATION OF CASE: Our current case showed a long-term benign course before the operation, although the subcutaneous tumor was larger than 10 cm at presentation. The SFT was diagnosed by needle biopsy, and wide resection was performed. Histological findings showed proliferation of capillaries surrounded by masses of spindle-shaped cells without any cytologic atypia, and the percentage of MIB-1-positive nuclei was 2.1%. However, a rapidly enlarging recurrent tumor was observed 11 months after the operation. A second wide resection for the recurrent tumor was performed. Histologically, the tumor cells uniformly displayed significant cytologic atypia and pleomorphism, and had 40–50 mitoses per 10 high-power fields. The proportion of MIB-1-positive nuclei was 48%. Consequently, the tumor was diagnosed as a SFT with malignant transformation. DISCUSSION: The malignant transformation described in past studies showed high-grade areas within benign, low-grade, or intermediate-grade SFTs. Therefore, in contrast to our case, uniformly high-grade malignant histological findings at recurrence were not described. CONCLUSION: Even if a tumor is non-malignant during the clinical course, as confirmed by tissue biopsy, the possibility of tumor progression to high-grade sarcoma at recurrence should be considered, and the treatment strategy should be determined carefully.